Atención farmacéutica en la bibliografía nacional e internacional - Elodie Ouadahi (Fundación Pharmaceutical Care España, 2023)
Community pharmacy is the key to improving vitamin D levels.  Lopez-Carmona, F.; Toro-Ruiz, Gomez-Guzman, A. M.; Valverde-Merino, M.; Piquer-Martinez, C.; Zarzuelo, M.I. Exploratory Research in Clinical and Social Pharmacy, Volume 9, 2023, 2667-2766. https://doi.org/10.1016/j.rcsop.2023.100224 Polish Patients' Needs and Opinions about the Implementation of Pharmaceutical Care in Diabetes. Waszyk-Nowaczyk, M.; Guzenda, W.; Kamasa, K.; Zielińska-Tomczak, Ł.; Cerbin-Koczorowska, M.; Michalak, M.; Przymuszała, P.; Plewka, B.  Int. J. Environ. Res. Public Health 2023, 20, 945. https://doi.org/10.3390/ijerph20020945 Evolving role of pharmacy technicians in pharmaceutical care services: Involvement in counselling and medication reviews. Iheanacho, C.O.; Adeyeri, O.; Eze, U.I.H. Exploratory Research in Clinical and Social Pharmacy, 5. 2022. 100113. 2667-2766. https://doi.org/10.1016/j.rcsop.2022.100113